2015
DOI: 10.1080/10242694.2015.1055936
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Syrian refugees on the labor market in neighboring countries: empirical evidence from Jordan

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…Similar to cash transfers, child labor has been examined across multiple development settings [ 44 46 ], however, data from humanitarian contexts is extremely sparse and generally limited to anecdotal information. As urban environments have become a more common setting for humanitarian crises, there is an increased risk that children will be used for begging, street vending, and other forms of exploitation [ 47 48 ]. There is a need to understand the prevalence, dynamics, and effective interventions to reduce this protection risk for children who have been displaced as well as children from affected host communities.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to cash transfers, child labor has been examined across multiple development settings [ 44 46 ], however, data from humanitarian contexts is extremely sparse and generally limited to anecdotal information. As urban environments have become a more common setting for humanitarian crises, there is an increased risk that children will be used for begging, street vending, and other forms of exploitation [ 47 48 ]. There is a need to understand the prevalence, dynamics, and effective interventions to reduce this protection risk for children who have been displaced as well as children from affected host communities.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the global refugee crisis, research has shown that refugees pose little challenge to skilled workers because most refugees seek career opportunities with low levels of skills (Scheve & Slaughter, 2001). For example, a recent study found that the influx of three million Syrian refugees in Jordan and Lebanon had little impact on the performance of labor markets in host countries (Fakih & Ibrahim, 2016). Countries with greater proportions of educated citizens are more likely to hold accepting attitudes toward refugees, either because education fosters more egalitarian values (Chatard & Selimbegovic, 2007), or most citizens feel less threatened by refugees as their access to various resources remains intact.…”
Section: Institutional Influence and Nbs Theorymentioning
confidence: 99%
“…There are few published academic studies that have examined the mental health of the Syrian refugees who live in the host communities of Jordan. Most studies in this area have delved into Syrian refugees’ physical health (Collins et al., ; Doocy et al., 2017; Bucak, Almis, Benli, & Turgut, ), the pressure on the host countries’ health care systems, and the shortage of services provided by humanitarian organizations (Coutts & Fouad, ; Coutts, Fouad, & Batniji, ; Fakih & Ibrahim, ; Quosh et al., ). We were unable to find studies related to the traumatic experiences of Syrian refugees who live in the host communities of Jordan, or to the mental health consequences that result from the challenges they face.…”
mentioning
confidence: 99%
“…In addition to survival challenges, the influx of refugees has tremendously increased the demand on schools, sanitation, housing, food, energy, and water in Jordan (Fakih & Ibrahim, ), which has resulted in Jordanians, who at first welcomed refugees, becoming increasingly hostile as their resources are tremendously strained. For example, Syrians are not granted work permits in Jordan.…”
mentioning
confidence: 99%